The case of Vincent Lambert: Who Will Be Able to Unravel the Knot? (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
The focus of the contribution concerns the jurisdictional developments in the case of Vincent Lambert and deals with the recent legislative amendments that the lonetti loi introduced with regards to end of life decisions and to the respect of patients’ advanced directives.
Keywords: end of life issues; advanced directives; patient will; France.